Biodiversity and ecology of Hirudinea (Annelida) from the Natural Reserve of Isla Martín García, Río de la Plata, Argentina - II. César (Brazilian Journal of Biology)
The Island of Martin Garcia lies at the confluence of the Uruguay and Paraná Rivers (upper Río de la Plata). This island is an outcrop of the crystalline basement. Due to basalt exploitation the island exhibits several ponds covered by carpets of free-floating macrophytes. Seven major environmental variables were measured: water and air temperature, percentage of oxygen saturation, dissolved oxygen, electrical conductivity, total dissolved solids and pH. Eleven leech species were found, Helobdella striata, H. diploides, H. adiastola and H. hyalina were new records. UPGMA clustering of species based on their occurrence in different ecological conditions revealed three main species groups. Canonical Correspondence Analysis (CCA) explained 97.2% of the correlation between species and environmental variables. H. triserialis shows the widest range of tolerance, H. hyalina shows positive relationships to conductivity; H. diploides shows a high correlation with dissolved oxygen, H. striata, H. lineata, and S. similis are negatively correlated with water temperature, and H. simplex is positively correlated with pH. Relationships between the species richness (S) and the sampling sites were negatively correlated with water temperature and positively correlated with dissolved oxygen. Leech biodiversity from the water bodies of Martín García Island, shows a great diversity of species and a wide plasticity regarding the characteristics of the environmental factors considered.